Comparison of Open Mesh versus Non-mesh for Indirect Inguinal Hernia Repair - Reanpinyawat, Chairat (Journal of Health Science of Thailand, 2018)
Thirtyone indirect inguinal hernia patients were divided randomly into two groups in order to compare outcomes of two different methods of using mesh and non-mesh during two year period from January 1, 2005 to December 31, 2006. The results of the open operative repair with mesh and non-mesh for indirect inguinal hernia were recorded. Sixteen patients in groups 1 received non-mesh inguinal hernia repair employing Bassini method. While those 15 patients in groups 2 received mesh inguinal hernia repair. There were 2 patients classified as loss follow up after operation, 1 patient in each group therefore the only 29 patients (15 patients in non-mesh group and 14 patients in mesh group) could complete the study. The results showed that no significant differences (p > 0.05) were seen in age, length of hospital stay except for significant difference (p < 0.05) in operation times, and post operative pain.